Fine Needle Aspiration Cytology with the Assistance of Radiological Tools in the Diagnosis of Deep-Seated Lesions - Dhakal, R.; Makaju, R.; Karki, S.; Dhakal, B. (Kathmandu University Medical Journal, 2021)
Background Fine needle aspiration (FNA) with radiological assisted tools such as ultrasonography (USG) and computed tomography (CT) are effective in obtaining high yield aspiration of tissues located in technically difficult places such as deep-seated. It is a simple outpatient procedure with low cost as compared to surgical biopsies. Objective To study the cytomorphological features of deep-seated lesions according to the site of occurrence, and to categorize them with respect to age, sex and behavior of lesions. Method This was a descriptive cross-sectional study of 125 patients who underwent image-guided fine needle aspiration cytology of deep-seated lesions. The study was conducted in the Department of Pathology and Department of Radiodiagnosis, Dhulikhel Hospital- Kathmandu University Hospital, between January 2017 and December 2018. Under radiological guidance, aspiration was performed under negative pressure, and adequate material was obtained. Smears were stained with Giemsa and Papanicolaou stain. The prepared slides were examined under a microscope. Result Of the 125 patients who underwent USG and CT-guided fine needle aspiration cytology (FNAC), 68(54.4%) were female and 57(45.6%) were male. The age of the patients ranged from 13 to 84 years. The maximum number of patients was above 50 years. The nature of lesions was categorized as malignant 78(62.4%), followed by 23(18.4%) inflammatory and benign 1(0.8%). Conclusion Image-guided fine needle aspiration cytology is a safe diagnostic procedure, as it provides real-time visualization of tip insertion in anatomical structures. It provides high yield and a better representation of the samples.